Factors-6

From Homeworkwiki

Jump to: navigation, search

Factorize :

(i) x 2 + 7 x + 6 + p x + 6 p

(ii) 3 (2 a - b) 2 - 5 (2 a - b) - 8

Solution :

(i) x 2 + 7 x + 6 + p x + 6 p

= x 2 + 6 x + x + 6 + p x + 6 p [Factorizing x 2 + 7 x + 6]

= x (x + 6) + 1 (x + 6) + p (x + 6)

= (x + 6) (x + 1 + p)

(ii) 3 (2 a - b) 2 - 5 (2 a - b) - 8

= 3 x 2 - 5 x - 8 [Taking : 2 a - b = x]

= 3 x 2 - 8 x + 3 x - 8

= x (3 x - 8) + 1 (3 x - 8)

= (3 x - 8) (x + 1)

= [3 (2 a - b) - 8] (2 a - b + 1) [Substituting the value of x]

= (6 a - 3 b - 8) (2 a - b + 1)

Personal tools
McAfee SECURE sites help keep you safe from identity theft, credit card fraud, spyware, spam, viruses and online scams